2000
DOI: 10.1038/labinvest.3780062
|View full text |Cite
|
Sign up to set email alerts
|

Two Different Types of Sialoadenitis in the NOD- and MRL/lpr Mouse Models for Sjögren's Syndrome: A Differential Role for Dendritic Cells in the Initiation of Sialoadenitis?

Abstract: SUMMARY: Sjö gren's syndrome is an autoimmune disease that primarily affects the salivary and lacrimal glands. In these glands, focal lymphocytic infiltrates develop. Little is known about the initiation of this autoimmune disease. Antigen-presenting cells (APC) such as dendritic cells (DC) can play a role in the initiation of autoimmunity. To date, no data on the presence of DC in Sjö gren's syndrome are available. Several mouse strains, the nonobese diabetic (NOD) and the MRL/lpr mouse, can be used as models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 41 publications
(38 reference statements)
3
42
2
Order By: Relevance
“…Moreover, Fas, FasL, and Bcl-2 were also more strongly expressed at birth and were localized around ducts and acini. Intriguingly, all these structures resembled nerves, which are known to be present in these exact locations (Kusakabe et al, 1997), as are the first infiltrating antigen-presenting cells (van Blokland et al, 2000), a finding reminiscent of our present data in the pancreas. Moreover, studies on salivary hypofunction in NOD mice showed autoantibodies and T-cell reactivity with neuron-specific reactivity (Esch and Taubman, 1998).…”
Section: Innervation In Neonatal Mousesupporting
confidence: 71%
“…Moreover, Fas, FasL, and Bcl-2 were also more strongly expressed at birth and were localized around ducts and acini. Intriguingly, all these structures resembled nerves, which are known to be present in these exact locations (Kusakabe et al, 1997), as are the first infiltrating antigen-presenting cells (van Blokland et al, 2000), a finding reminiscent of our present data in the pancreas. Moreover, studies on salivary hypofunction in NOD mice showed autoantibodies and T-cell reactivity with neuron-specific reactivity (Esch and Taubman, 1998).…”
Section: Innervation In Neonatal Mousesupporting
confidence: 71%
“…In contrast, the implication of IL-18 in lymphomagenesis has not yet been clarified (41,42), and further prospective studies are needed to define the involvement of IL-18-expressing macrophages in the monoclonal B lymphocyte expansions that occur in patients with primary SS. Nevertheless, it may be of relevance that Th2-type cytokine reactions may be induced in vitro and in vivo by IL-18 in the absence of IL-12 (21,43), and such responses have been demonstrated to occur in patients with primary SS, with the intense accumulation of B cells or overt B cell lymphoma in the MSGs (12,44).…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of APC- derived and APC-recruiting cytokines and chemokines in the inflamed glandular structures of patients with primary SS, as well as in experimental mouse models of SS (35)(36)(37)(38)(39)(40), indirectly implicates APCs in the pathogenesis of SS. In addition, significant infiltration by classic APCs has been reported in the glandular lesions in mouse models of SS, and has been associated with increased expression of Th1-type cytokines and tissue dysfunction (37,41).…”
Section: Discussionmentioning
confidence: 99%
“…In the MRL/lpr mouse, another mouse model for Sjögren's syndrome (Hoffman et al, 1984), hardly any DC were present before the onset of sialoadenitis (van Blokland et al, 2000). This suggests that DC play an important role in the initiation of sialoadenitis in NOD mice, whereas in MRL/lpr mice their role may be limited.…”
mentioning
confidence: 84%